On a new genus and seven species of Chrysillini from China (Araneae: Salticidae: Salticinae) - Yang, Zhiyong; Wang, Weihang; Zhang, Junxia (Zootaxa, 2024)
A new genus of chrysilline jumping spiders, Qingattus gen. nov., is established for a new species from southern China: Qingattus wulan spec. nov. (♂♀). Three other new species of Chrysillini are described: Heliophanoides ultramarine spec. nov. (♂♀), Phintella chunfen spec. nov. (♂) and P. yi spec. nov. (♂). Newly recorded from China are Cosmophasis ombria (Thorell, 1877) (♂♀), Heliophanus chovdensis Prószyński, 1982 (♂♀), and Okinawicius tokarensis (Bohdanowicz & Prószyński, 1987) (♂♀).